One Cell at a Time: Advances in Single-Cell Methods and Instrumentation for Discovery in Aquatic Microbiology - Grujcic, Vesna; Taylor, Gordon T.; Foster, Rachel A. (Frontiers in Microbiology, 2022)
Studying microbes from a single cell perspective has become a major theme and interest within the field of aquatic microbiology. One emerging trend is the unfailing observation of heterogeneity in activity levels within microbial populations. Wherever researchers have looked, intra-population variability in biochemical composition, growth rates, and responses to varying environmental conditions have been evident and probably reflect coexisting genetically distinct strains of the same species. Such observations of heterogeneity require a shift away from bulk or ensemble approaches, and development of new methods or adaptation of existing techniques, many of which were first pioneered in other, disparate fields, e.g., material, physical and biomedical sciences. Many of these approaches were also initially optimized using model organisms. However, in a field with so few cultivable models, method development has been challenging, but has also contributed tremendous insights, breakthroughs, and stimulated curiosity. In this perspective, we present a subset of methods that have been effectively applied in studying microbes at the single cell level. Opportunities and challenges for innovation are also presented. We suggest future directions for aquatic microbiological research that will benefit from open access instrument infrastructures and highly interdisciplinary collaborations.